Reduced CD40 expression in B cell subsets of individuals with radiologically isolated syndrome - Keller, Christian W.; Stein, Kerstin; Vilaseca, Andreu; Villar, Luisa M.; Álvarez-Bravo, Gary; Protopapa, Maria; Shin, Josef; Fissolo, Nicolás; Martínez-Rodríguez, José Enrique; Quiroga-Varela, Ana; García-Sarreón, Alexis; Gutiérrez, Lucía; et al. (Frontiers in Immunology, 2025)
IntroductionB cells play a central role in multiple sclerosis (MS) pathogenesis, yet their activation profiles during the earliest disease stages remain incompletely characterized. We aimed to investigate the expression of the activation markers CD40 and CD71 across peripheral B cell subsets in individuals with radiologically isolated syndrome (RIS), and compare them to those with clinically isolated syndrome or MS (CIS/MS) and healthy controls (HC).MethodsPeripheral blood cells from individuals with RIS (n=21), CIS/MS (n=15), and HC (n=15) were analyzed by flow cytometry. CD40 and CD71 expression was assessed across major B cell subsets. Epstein-Barr virus (EBV) serologies were measured to explore associations with activation marker expression.ResultsCD40 expression was reduced on transitional, naïve, B cell subsets in RIS compared to CIS/MS and HC (p<0.001). CD71 expression remained stable across groups. CD40 expression was preserved in plasmablasts and regulatory B cells. No significant associations were observed between CD40 levels and EBV antibody titers.DiscussionIn this cross-sectional cohort, CD40 expression was lower on transitional, naïve, and memory B cell subsets in RIS compared to CIS/MS and HC, whereas plasmablasts and regulatory B cells were comparable. This pattern is consistent with an altered costimulatory state in early, asymptomatic disease and warrants longitudinal studies to determine its clinical relevance.